2016
DOI: 10.1016/j.chiabu.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Victimization and psychopathic features in a population-based sample of Finnish adolescents

Abstract: We examined different forms of victimization experiences in relation to psychopathic features and whether these associations differed in boys and girls among 4855 Finnish school adolescents aged 15-16 years. Psychopathic features were measured with the Antisocial Process Screening Device- Self Report (APSD-SR). Victimization was assessed with questions about violent and abusive experiences across lifetime and within the last 12 months. Results from linear regression analysis showed that victimization was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Longitudinal research also will allow investigations into the mechanisms by which posttraumatic risk‐seeking develops. For example, a growing body of the literature suggests that callous traits, which are characterized by a lack of empathy and remorse, can be understood as a form of emotional desensitization in the aftermath of exposure to childhood trauma, maltreatment, and victimization (Baskin‐Sommers & Baskin, ; Kimonis, Fanti, Isoma, & Donoghue, ; Krischer & Sevecke, ; Saukkonen et al, ), and the PTSS resulting from these experiences (Bennett & Kerig, ; Tatar, Cauffman, Kimonis, & Skeem, ). Significantly, callous traits not only predict the most aggressive and recalcitrant forms of offending but also are associated with risky sexual behavior, substance misuse, and sensation‐seeking among justice‐involved boys (Thornton et al, ).…”
Section: Implications Of the Risk‐seeking Construct For Researchmentioning
confidence: 99%
“…Longitudinal research also will allow investigations into the mechanisms by which posttraumatic risk‐seeking develops. For example, a growing body of the literature suggests that callous traits, which are characterized by a lack of empathy and remorse, can be understood as a form of emotional desensitization in the aftermath of exposure to childhood trauma, maltreatment, and victimization (Baskin‐Sommers & Baskin, ; Kimonis, Fanti, Isoma, & Donoghue, ; Krischer & Sevecke, ; Saukkonen et al, ), and the PTSS resulting from these experiences (Bennett & Kerig, ; Tatar, Cauffman, Kimonis, & Skeem, ). Significantly, callous traits not only predict the most aggressive and recalcitrant forms of offending but also are associated with risky sexual behavior, substance misuse, and sensation‐seeking among justice‐involved boys (Thornton et al, ).…”
Section: Implications Of the Risk‐seeking Construct For Researchmentioning
confidence: 99%
“…Intervention strategies for psychopathy typically relied on the use of cognitive behavioral therapy to mitigate the likelihood of future criminal behavior (Polaschek & Skeem, 2018). Focusing instead on how to modify features of psychopathy through improvements in maturation may be a more holistic approach that addresses a broader set of negative outcomes associated with psychopathy (Hemphälä & Hodgins, 2014;Herpers et al, 2016;Saukkonen et al, 2016). Rocque's (2015) IMT was used as a framework for the measurement of different components of psychosocial, adult social role, and identity maturation among boys and girls from the Pathways to Desistance Study (n ¼ 1,354).…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathy is associated with various negative behavioral, health, and social outcomes (Hemphälä & Hodgins, 2014; Herpers et al, 2016; Saukkonen et al, 2016). This has lead to calls to identify factors that influence change in features of psychopathy (see Lynam et al, 2008; Reidy et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Indeed, we only identified one study of a community sample of youth that examined associations between child abuse and victimization and psychopathic features. Drawing on data from 4,855 school adolescents in Finland, Saukkonen et al (2016) found that victimization or abuse experiences were stronger predictors of psychopathic personality among girls than boys. However, the gendered effects were only seen for lifetime victimization experiences.…”
Section: The Abuse-psychopathy Relationship Among Femalesmentioning
confidence: 99%